1981
DOI: 10.1007/bf00139585
|View full text |Cite
|
Sign up to set email alerts
|

Hermansky-Pudlak syndrome: albinism with lipofuscin storage

Abstract: The Hermansky-Pudlak Syndrome, a "tyrosinase positive' form of oculocutaneous albinism, is a triad comprising albinism, a hemorrhagic diathesis and ceroid-lipofuscin storage. A pedigree is presented showing consanguinity with a pattern of pseudodominance. Electroretinography in two isolated Hermansky-Pudlak subjects was distinctly abnormal, showing decreased rod and cone responses (as well as abnormal flicker fusion responses) in one patient, and reduced photopic and scotopic responses in another. The decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Due to the small number of cones in the rodent retina, very little data are available on cone function in pigmented animals, and even less in albino animals. However, in human ocular albinism, Fagadau et al (1981) reported reduced cone responses as well as abnormal flicker fusion responses, supporting our findings in the albino mouse retina.…”
Section: Cone Erg Analysis In Pigmented and Albino Animals During Matsupporting
confidence: 89%
See 1 more Smart Citation
“…Due to the small number of cones in the rodent retina, very little data are available on cone function in pigmented animals, and even less in albino animals. However, in human ocular albinism, Fagadau et al (1981) reported reduced cone responses as well as abnormal flicker fusion responses, supporting our findings in the albino mouse retina.…”
Section: Cone Erg Analysis In Pigmented and Albino Animals During Matsupporting
confidence: 89%
“…Thus, in human subjects, rods are susceptible to age-related degeneration, whereas cones are more stable. Patients with albinism appear to have fewer cones resulting in reduced photopic visual acuity (Summers, 1996), and patients with ocular albinism have been reported to exhibit defects in both rod and cone pathways (Fagadau et al, 1981;Carlson et al, 1991).…”
Section: The Aging Mouse Retina As a Model System For Normal Human Agingmentioning
confidence: 99%
“…26,36,[40][41][42][43] All patients with HPS reported in the ophthalmic literature have had nystagmus. [7][8][9][10][11][12] In contrast, 3 of our patients (11%) did not have clinically noticeable oscillations. These patients had a better visual acuity range, as well as more iris and retinal pigmentation than the rest.…”
Section: Eye Movement Characteristicsmentioning
confidence: 81%
“…Patient 26 was not assessed because of the young age and patient 27 because of severe pulmonary fibrosis requiring constant treatment with oxygen. The eye movements of 10 individuals (patients 1, [8][9][10][11][12][13]15,17,18) were recorded using a magnetic search coil technique (Table 1). 14 rear-projected onto a tangent screen at 1 m. With the ISCAN and Ober 2 systems, patients viewed a crossshaped target subtending 1 degree in horizontal and vertical meridian, which was projected onto a 40-inch plasma monitor 1 m from the patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation